STRUKTUR PERKEMBANGAN DASAR TUMBUHAN : STUDI EMBRIOGENESIS PADA EMBRIO ARABIDOPSIS - Pulungan, Nur Aminah; Wan Syafi’i (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Embryogenesis in angiosperms is a critical phase that determines the success of seed development and subsequent plant viability. The analysis shows that embryogenesis proceeds through coordinated stages that include zygote formation, tissue differentiation at the dermatogen and globular stages, and the formation of the shoot apical meristem (SAM), root apical meristem (RAM), and cotyledons at the heart stage. The seed coat, derived from maternal tissue, also undergoes functional differentiation, including the formation of secondary cell walls and the accumulation of protective metabolites such as flavonoids. A comprehensive analysis indicates that Arabidopsis embryogenesis is an integrative process controlled by genetic regulation, interactions between seed compartments, and interdependent metabolic and structural controls. These findings confirm that successful embryo development depends not only on morphogenesis but also on the coordination between the embryo, endosperm, and testa in forming a vigorous and adaptive seed.